THE PLAY OF MONOLOGUE PUTU WIJAYA; CREATIVE PROCESS AND PERIOD OF WRITING - ENRICO ALAMO (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
Putu Wijaya is one of the most important Indonesian playwrights in writing, both; short stories, novels, drama scripts, and even monologue scripts. At the moment the manuscript is published, published 118 titles published in the book